Evaluation of Neurofibromatosis Gene Expression in Non-Hereditary Breast Cancer - Kavousi, Mahsa; Smailzadeh, Fatemeh; Fallah Mehrabadi, Jalil; Geranpayeh, Lobat (Novelty in Biomedicine, 2023)
Background: Breast cancer is the most common cause of death in women. Studies have shown that changes in neurofibromatosis gene expression can cause breast cancer. The aim of this study was to investigate the change of neurofibromatosis type 1 gene expression in non-hereditary breast cancer using real time PCR. Materials and Methods: In this study, 160 tissue samples were collected from patients following ethical principles. After lysis of tissues, extraction of RNA and synthesis of cDNA was performed. The amount of gene expression changes was investigated. Results: The results showed that the level of NF1 gene expression was dependent on the stages of the disease and as the stages progress, the level of expression of this gene showed a significant decrease. Conclusion: The use of gene biomarkers can help to diagnose and treat diseases faster. Along with examining other candidate genes, using NF1 gene expression analysis in breast cancer patients can be a suitable option for diagnosing the stages of disease progression.